PEMANFAATAN AREA SUDUT RUANG GUNA MENUNJANG FASILITAS PEMBELAJARAN DI TAMAN BELAJAR KITA - Yusuff, Adisti Ananda; Widyastuti, Putri Anggraeni; Huddiansyah, Huddiansyah (Jurnal Pengabdian Masyarakat AbdiMas, 2021)
Taman Belajar  Kita Is a place of learning non formal founded as an alternative training ground for children in the neighborhood during the pandemic now.Established to facilitate in parents who had difficulty in watching his sons did, learning at home , In addition Taman Belajar Kita also provided a basis for children drop out free school .And the facilities provided by the owner of the learning we do own limited both in place and facility .Taman Belajar Kita  have two classroom with small size used as a place of learning for children with learning activities there. So we are limited in view of the people university one devotion to feel moved to help when we learned in the garden .The lack of a place to store the works of the result of the students is taking us in the designer educator who feel the need to intervene to help . the unconditional class make us to trying to provide facilities needed to help the learning process in the us to learn better in the future , so the students become more spirit and motivated in learning and create something creative. Keywords : learning facilities, corner room, interior design